Game Insight Skills as a Predictor of Talent for Youth Soccer Players - de Joode, Tom; Tebbes, Drewes J. J.; Savelsbergh, Geert J. P. (Frontiers in Sports and Active Living, 2021)
Perceptual-cognitive skills are found to be important factors for soccer players. The aim of this study was, therefore, to find within-group differences for game insight in an elite group of youth soccer players by means of a Game Insight inDicator (GID). In addition, prospective value of perceptual-cognitive skills was examined by following the trajectory of the participants. The GID consisted of films clips that show game situations. The task of the players was to predict the trajectory and destination of the ball and move towards the correct position to receive the pass of a teammate. The film clips stopped 80ms before, at and 80ms after the foot-ball contact of a teammate. We also sougth to valide the GID against game performance. Participants were talented soccer players 11-13 years old and playing at the elite level for their age. Based on eight independent elite-coach judgements, two groups were created: highly talented players (HT) and less talented players (LT). The coach ratings were supported by a significant difference between the two groups based on the objective notational analysis of their game performance in 4 vs. 4, and 11 vs. 11 matches. With respect to the GID, a significant interaction effect for group (HT vs LT) by occlusion time (-80, 0-, +80ms) was found, showing that the HT performs better than the LT in 0ms and +80ms condition. In addition, GID scores were compared with soccer level at the mean age of 19. Longitudinal data did not show significant differences between elite and sub-elite. Overall, the GID was found to be a valid and useful indicator for player’s anticipating the ball’s trajectory and destination at age 11-13, but failed to predict the players level at age 19. The latter indicates how difficult it is to predict talent development